Effect of Organizational Climate and Participation in Budgeting on Employee Performance - Kadir Ashadi L. Diab, Abdul; Akib, Akib; Insawan, Husain; Sulaiman, Nasrullah (KnE Social Sciences, 2022)
The objectives of this study were to: 1) examine the impact of organizational climate on employee performance at IAIN Kendari; 2) analyse the influence of budgetary participation on employee performance; 3) evaluate the impact of organizational climate and participation in budget preparation on employee performance; and 4) assess the role of Islamic economics on organizational climate, budgeting participation, and employee performance. Data were collected using a survey, applying a quantitative approach. The research sample consisted of 55 employees of various faculties, units and institutions. After assessing normality, linearity, multicollinearity and autocorrelation, data analysis involved descriptive and inferential analysis. Simple regression analysis and path analysis were used to test the hypotheses. The findings revealed that: 1) organizational climate had a positive and significant impact on employee performance with a 62.6% contribution; 2) participation in budgeting had a positive and significant impact on employee performance with a 40% contribution; and 3) the combination of organizational climate and participation in budgeting had a positive and significant impact on employee performance with a 40% contribution. Keywords: organizational climate, participation, budgeting, employee performance, sharia economy